Development of e-learning media with class room online on device installation materials LAN for student SMK - Kamirin Kamirin; Olgi Gerieska; Kasman Rukun; Asrul Huda (International Conferences on Educational, Social Sciences and Technology)
Information and computer technology has developed along with the globalization, where a learning system must integrate with the use of computers and the Internet. The purpose of this research is on the LAN device installation and to know the validity and practicalities of the media. This is according to Van Den Akker's consisting of: requirements analysis, design, evaluation and revision. This research resulted from the media in the form of E-Learning with Classroom Online that is validated by a validate with criteria very well 94.28%. A Testing for practicalities is done with 20. The result of the testing for practicalities is stated that the e-learning Classroom Online is good categorized with an average score of 83% in terms of the interest of the students, the process of increasing its use, liveliness, time and student evaluation. E-learning in the Classroom Online as one of the alternative media learning materials on the installation of the device for the LAN in the vocational school.